2015
DOI: 10.4137/jmecd.s17497
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceived Value of Anatomy Pedagogy, Part II: Clinical Practice and Assessment

Abstract: We describe student beliefs of how anatomy education influenced their preparation for standardized clinical assessments and clinical skills. We conducted three annual surveys of students of the David Geffen School of Medicine (DGSOM) at the University of California Los Angeles (UCLA) and students of the University of California, Riverside (UCR)/UCLA Thomas Haider Program in Biomedical Sciences from 2010 to 2012. Students were asked, "What specific knowledge or skills did you learn from your gross anatomy exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In our study, students reported that virtual dissection enhanced their understanding of the clinical relevance of anatomy and pathologic conditions suggesting that that virtual dissection can be used to teach anatomy in a more clinically relevant context so that students can apply what they have learned in the laboratory directly to patient encounters. This observation is corroborated by a recent study, that found that students did not value anatomy pedagogy taught outside of clinical context (30). Although the cases selected our Virtual Dissection Curriculum were from the electronic database associated with our virtual dissection system, local institutional cases can also be uploaded, allowing for maximum flexibility when designing curricula.…”
Section: Discussionsupporting
confidence: 66%
“…In our study, students reported that virtual dissection enhanced their understanding of the clinical relevance of anatomy and pathologic conditions suggesting that that virtual dissection can be used to teach anatomy in a more clinically relevant context so that students can apply what they have learned in the laboratory directly to patient encounters. This observation is corroborated by a recent study, that found that students did not value anatomy pedagogy taught outside of clinical context (30). Although the cases selected our Virtual Dissection Curriculum were from the electronic database associated with our virtual dissection system, local institutional cases can also be uploaded, allowing for maximum flexibility when designing curricula.…”
Section: Discussionsupporting
confidence: 66%
“…Also, as the students gain knowledge later and later in their clinical years, their mind-set about the role of anatomy may change. 7 Schoeman and Chandratilake 8 have introduced the term "anatomy competence" and define it as the possession of appropriate anatomy knowledge, and practical and clinical application of this knowledge.…”
Section: Introductionmentioning
confidence: 99%